The dynamics of civic education lectures in shaping the democratic character of students at ahmad dahlan university - Sukmayadi, Trisna; Abdulkarim, Aim; Komalasari, Kokom; Masyitoh, Iim Siti (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Civic Education has a strategic role in shaping the democratic character of students. This research aims to analyze the factual conditions of PKn lectures at Ahmad Dahlan University and measure the level of democratic character of students. The research method used is a mixed method by combining a quantitative approach with data collection techniques through questionnaires, interviews and observations of students. The results showed that the Civic Education Lecture at Ahmad Dahlan University played a significant role in shaping the democratic character of students, although there were aspects that needed improvement, such as the involvement of expert sources. The democratic character of students is also high, but active participation needs to be increased. This research highlights the importance of developing more interactive learning methods, such as problem-based projects and debate simulations, as well as collaboration with practitioners to enrich students' insight into democracy